Societal Impacts of Open Government Data Use: Systematic Literature Review and Altmetric Evaluation - Emigawaty, Emigawaty; Adi, Kusworo; Rochim, Adian Fatchur (DESIDOC Journal of Library & Information Technology, 2023)
The purpose of this research is to investigate the impacts of Open Government Data (OGD) use on the societal-economic sphere and to identify possible gaps in the literature between its several categories. Therefore, this paper led to a deliberate literature study of the OGD research that primarily collected on empirical earlier papers. We systematically reviewed 88 reputable articles connected with the societal impacts of OGD use utilising Scopus Gateway from 2012 to 2022. We followed the Prefered Reporting Items for Systematic Review and Meta-Analysis (PRISMA) Protocol, and several software tools such as Mendeley, Publish or Perish, and VOSViewer to support the literature review process. This research provides several essential statistical views related to the social impact in the OGD field using Altmetric. The result shows that there were 26 categories of the OGD used for the societal consequences, with 8 main keywords most frequently used by the authors. Additionally, the highest number of authors who contributed to the discussion of social impact data, especially on the issue of open government, was 19, recorded in 2012. A number of topics overwhelmed the discussion of social impacts, namely, open government, citizen engagement, socio-economic value, and transparency in the period of 2015 and 2017.